Glass-based LED system for indoor horticulture: enhanced plant growth through Sm3+ and Tm3+ co-doped luminescent glasses - Ekim, Utku; Ilter, Emre; OEzan, Emirhan; Temuerhan, Yusuf; Ersundu, Miray Celikbilek; Ersundu, Ali Ercin (ROYAL SOC CHEMISTRY, 2023)
This study addresses the challenges of sustainable and efficient agricultural practices in the face of climate change and the destruction of agricultural lands by presenting the development of a novel plant growth LED based on Sm3+ and Tm3+ co-doped luminescent glasses with color-converting properties that emit blue and red light, resulting in an increased rate of photosynthesis and density of photosynthetically active radiation reaching the harvesting pigments. The developed LED exhibits photoluminescence (PL) peak positions ranging from 454 to 648 nm, with a spectral coverage of 50% and 39% of the absorption regions of chlorophyll a and chlorophyll b, respectively, resulting in an impressive 56% photoluminescence quantum yield (PLQY). Furthermore, the developed plant growth LED demonstrates robust performance, remaining unaffected by temperature cycles and extended operation periods. Using Romaine lettuce cultivated under identical conditions, a comparative study between the developed LED and commercially available plant growth LED is conducted, with the designed LED showing significant improvements in plant growth characteristics, including increased plant height, weight, number of leaves, and enhanced levels of chlorophyll a, chlorophyll b, and carotenoid content, while the root diameter is reduced, and the shoot-to-root ratio is diminished in comparison to the commercially available plant growth LED. The paper also compares the performance of Sm3+ and Tm3+ co-doped luminescent glass-based plant growth LED with other reported plant growth LED designs using different luminescent materials, exploring the impact of PLQY, PL position, and plant growing conditions. The results suggest that the developed LED system offers a more efficient and sustainable way of lighting for indoor horticulture and has significant implications for meeting the increasing food demands of the growing world population.
Keywords: ENERGY-TRANSFER PERFORMANCE; PHOSPHOR-IN-GLASS; HIGH-POWER; OPTICAL-ABSORPTION; EMISSION PHOSPHOR; CLIMATE-CHANGE; RED EMISSION; PHOTOLUMINESCENCE; LIGHT; BLUE; Chemistry; Physics